High-temperature tribological properties of diamond-like carbon films: A review - Zeng Qunfeng (De Gruyter, 2021)
The rapid development of aerospace industry has made more and more machinery parts of equipment working at high temperature. Due to the lubrication failure of lubricating oil and grease at high temperature, solid lubricant coatings are almost the only effective method to achieve super low friction at high temperature. In recent years, the tribological properties of diamond-like carbon (DLC) films have been extensively studied at high temperature. The present study reviews the microstructure of DLC films and the influence of doping different elements on the structure of DLC films. Second, the mechanical properties and thermal stability of pure DLC films and DLC doped with different elements are also described. DLC films have different microstructures and tribological properties by different preparation methods. Finally, the high-temperature lubrication failure mechanism of DLC films and the tribological properties of DLC films when doped with different elements are discussed from the macro and micro perspectives.